2013
DOI: 10.1038/pr.2013.92
|View full text |Cite
|
Sign up to set email alerts
|

Acute inflammation in young children inhibits C-type natriuretic peptide

Abstract: Background: C-type natriuretic peptide (CNP) is a paracrine growth factor critical in endochondral bone growth. Amino-terminal CNP (NTproCNP), measurable in plasma, correlates with growth-plate activity and can be used as a biomarker of growth velocity in children. Because severe inflammation in adults increases CNP, we studied CNP peptides and inflammatory markers in children with acute illness. Methods: Forty-two children aged 2 mo to 5 y with acute illness warranting admission to an acute assessment unit we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the only study which examined the effect of IL-1b on natriuretic peptide receptors in chondrocytes treated with CNP, the cytokine was reported to increase CNP levels and Npr3 expression, thereby augmenting potential beneficial effects mediated by Npr signalling 40 . In general, inflammation was previously shown to upregulate CNP levels but in children, peptide levels were found to be reduced 53 , presenting potential complications on growth relevant to young patients with Juvenile Idiopathic Arthritis (JIA). Since there is strong evidence for a role of endogenous CNP signalling in normal cartilage development, the potential therapeutic role for exogenous CNP in the treatment of skeletal growth disorders should be investigated further.…”
Section: Effect Of Inflammation On Cnp/npr Signallingmentioning
confidence: 99%
“…In the only study which examined the effect of IL-1b on natriuretic peptide receptors in chondrocytes treated with CNP, the cytokine was reported to increase CNP levels and Npr3 expression, thereby augmenting potential beneficial effects mediated by Npr signalling 40 . In general, inflammation was previously shown to upregulate CNP levels but in children, peptide levels were found to be reduced 53 , presenting potential complications on growth relevant to young patients with Juvenile Idiopathic Arthritis (JIA). Since there is strong evidence for a role of endogenous CNP signalling in normal cartilage development, the potential therapeutic role for exogenous CNP in the treatment of skeletal growth disorders should be investigated further.…”
Section: Effect Of Inflammation On Cnp/npr Signallingmentioning
confidence: 99%
“…It is not about chronic diseases or chronic conditions are known to slow down growth, but also about acute and short-term illnesses. Prickett et al, investigating the concentration of NTproCNP and CNP in pre-school children with acute infection, have shown that the concentrations of both indicators are reduced, which suggests that the infection can slow down bone growth clinically unnoticeably [37]. Topçu et al investigated the NT-proCNP plasma concentration in the overweight or obese, in comparison to normal weight children.…”
Section: Discussionmentioning
confidence: 99%
“…The obvious signs and symptoms of these diseases make their presence unlikely to confound interpretation. However, acute inflammation, which appears to lower NTproCNP in young children [45], could be overlooked in some settings. Reports of lower levels of CNP products in obese adolescents [46, 47] have not been supported by a more formal study where the crucial impact of age (and therefore height velocity) was taken into account [30].…”
Section: Evidence That Plasma Cnp Products Correlate With Skeletal Grmentioning
confidence: 99%